Construction of a Molecularly Imprinted Sensor Modified with Tea Branch Biochar and Its Rapid Detection of Norfloxacin Residues in Animal-Derived Foods - Shujuan Chen; Yiting Zhu; Jing Han; Tianyi Zhang; Runwen Chou; Aiping Liu; Shuliang Liu; Yong Yang; Kaidi Hu; Likou Zou (Foods, 2023)
Norfloxacin (NOR) is a common antibiotic used in humans and animals, and its high levels can cause intolerance or poisoning. Therefore, NOR levels in animal-derived foods must be monitored due to potential side effects and illegal use phenomena. This research centered on the development of an environmentally friendly electrochemical sensor for NOR detection. Potassium carbonate activated tea branch biochar (K-TBC) as an efficient use of waste was coated on the surface of glassy carbon electrode (GCE), and a molecular-imprinted polymer (MIP) layer was subsequently electropolymerized onto the modified electrode. NOR was used as template molecule and o-phenylenediamine (o-PD) and o-aminophenol (o-AP) were used as bifunctional monomers. The electrochemical sensor was built and its electrochemical behavior on NOR was investigated. The sensor demonstrated an excellent linear current response to NOR concentrations in the ranges of 0.1–0.5 nM and 0.5–100 nM under ideal experimental circumstances, with a detection limit of 0.028 nM (S/N = 3). With recoveries ranging from 85.90% to 101.71%, the designed sensor was effectively used to detect NOR in actual samples of milk, honey, and pork. Besides, the fabricated sensor had low price, short detection time, good selectivity and stability, which can provide a theoretical and practical basis for the actual monitoring of NOR residues.